PENGARUH LAMA PENYIMPANAN TELUR HERBAL AYAM RAS FASE KEDUA PADA SUHU REFRIGERATOR TERHADAP PENURUNAN BERAT TELUR, DIAMETER RONGGA UDARA, DAN INDEKS ALBUMEN - Ahmad Yosman Arbi; RR Riyanti; Dian Septinova; Khaira Nova (Jurnal Riset dan Inovasi Peternakan (Journal of Research and Innovation of Animals), 2021)
This research aimed to determine the effect of storage time of herbal eggs of layer second phase at a temperature of refrigerator on egg weight, air cavity diameter, and albumen index and to find out the best storage time for the herbal eggs quality. This research was conducted on 7 October - 4 November 2020 at the Animal Production Laboratory, Department of Animal Husbandry, Faculty of Agriculture, University of Lampung. This study used a completely randomized design method (CRD) with 5 treatments of egg storage time for 0, 1, 2, 3, and 4 weeks. The data obtained were analysed using analysis of variance (ANOVA). If there was a significant effect of the ANOVA, the Least Significant Difference (LSD) test was carried out at 5% level. The results of this study indicated that the herbal egg storage time treatment had a significant effect (P <0.05) on the decrease of egg weight, air cavity diameter, and albumen index. The 1 week storage period gave the best effect on the lowest egg weight reduction, namely 0.90%, the lowest air cavity diameter (1.752 cm), and the highest albumen index (0.061) compared to the storage time of 2, 3, and 4 weeks. Keywords: Albumen index, Air cavity diameter, Egg weight, Refrigerator temperature, Storage time